Regulation of neuron accuracy by modulation of potassium channels - Kaczmarek, Leonard (Henry Stewart Talks, 2011)
Changes in excitability, Classes of potassium channels, Temporal accuracy, Slack and Kv3.1 channels, Elimination of Kv3.1, Effect of acoustic stimulation on Kv3.1 phosphorylation, Sodium-activated potassium channels, 3-D structure of Slack-B channels, Is the C-terminus of Slack a Na+-dependent regulator of translation?
Updated at 2021/03/08